A unimolecule nanopesticide delivery system applied in field scale for enhanced pest control - Xingye Li; Xinyue Wang; Changjiao Sun; Anqi Wang; Changcheng An; Ningjun Li; Yue Shen; Jiachong Hu; Huihui Liu; Jing Xie; Dan Luo; Yan Wang (Nature Communications)
Abstract Nanopesticides provide immense potential in reducing pesticide use and promoting sustainable agriculture for their enhanced pesticidal efficacy. Nano-enabled delivery systems can enhance pesticide penetration into both insects and leaves through their unique nanoproperties, in particular their small size. However, it remains a great challenge to achieve unimolecular formulations in water-based processes in order to take full advantages of nanoproperties. Here, using ionic liquid, we fabricate unimolecular nanopesticides (about 3 nm in average diameter) in a water-based process, termed unimolecule-nanopesticide delivery system. Guided by the density functional theory calculations, we successfully convert various traditional pesticides into the unimolecule-nanopesticide system, significantly enhancing cellular uptake, insect-dermis translocation, and leaf-cuticle penetration of pesticides. Furthermore, we improved field efficacy against multiple pests using the unimolecule-nanopesticide system. Importantly, the unimolecule-nanopesticide system utilizes only industry-grade raw materials that are Generally Recognized as Safe by the US Food and Drug Administration. We believe our unimolecule-nanopesticide system represents a water-based and facile-manufactured platform for other conventional pesticides to achieve high-efficiency field-scale plant protection.